Development of a Mindfulness-Based Coping Skills Training Package for Cancer and Its Effectiveness on Reducing Stress, Blood Cortisol Levels, and Psychological Self-Efficacy in Women with Breast Cancer in Bandar Abbas (A Mixed-Methods Study) - Karimpour, Shirin; Haji Alizadeh, Kobra; Zarei, Eghbal (Psychology of Woman Journal, 2026)
Objective: This study aimed to design and evaluate the effectiveness of a mindfulness-based psychological coping skills training package in reducing stress and cortisol levels and enhancing psychological self-efficacy among women with breast cancer. Methods and Materials: The study employed a mixed-methods design in two phases. In the qualitative phase, semi-structured interviews with 12 patients and psychology experts, alongside thematic analysis and literature review, were conducted to identify core dimensions of coping needs. The content and structure of the package were developed and validated using the Delphi method with 15 experts. The final program comprised ten 90-minute sessions focusing on mindfulness practice, adaptive coping strategies, and stress management skills. In the quantitative phase, a quasi-experimental design with pretest–posttest, control group, and two-month follow-up was applied. Thirty women with breast cancer, aged 20–45, were purposively sampled and randomly assigned to experimental (n = 15) and control (n = 15) groups. Data collection involved the Perceived Stress Scale, the Psychological Self-Efficacy Scale, and blood cortisol measurement. Data were analyzed using repeated measures ANOVA in SPSS 26. Findings: The intervention group showed a significant reduction in perceived stress scores compared to the control group (p < .001), with improvements sustained at follow-up. Cortisol levels also decreased significantly in the experimental group across posttest and follow-up (p < .001). Psychological self-efficacy scores increased markedly after the intervention (p < .001), indicating enhanced coping capacity. The interaction effects confirmed that improvements were specific to the experimental group. Conclusion: The mindfulness-based coping skills training package effectively reduced stress and cortisol levels and improved psychological self-efficacy in women with breast cancer, underscoring its potential as a complementary intervention to enhance psychological adaptation and overall quality of life in oncology care.